Sudden cardiac arrest as a result of anterior and lateral myocardial infarction at 16 weeks of gestation - case report - Justyna Wojcik; Karolina Obuchowska; Aleksandra Obuchowska; Alicja Ozga; Arkadiusz Standyło; Żaneta Kimber-Trojnar; Bożena Leszczyńska-Gorzelak (Kazimierz Wielki University, 2020)
Sudden cardiac arrest (SCA) is defined as a significant impairment of the mechanical function of the heart muscle, characterized by the patient's lack of response to stimuli, no perceptible pulse and apnea or agonal breathing, most often caused by acute coronary syndrome (ACS). ACS during pregnancy is a rare phenomenon and its incidence increases with the age of giving birth.The most common cause of ACS in pregnancy are typical changes in the etiology of atherosclerosis or coronary artery thrombosis. Other factors increasing the risk of a heart attack are arterial hypertension, diabetes, obesity and lipid disorders.     To describe a rare clinical case and demonstrate the importance of maintaining cardiac vigilance in pregnant patients.     A 32-year-old patient, at 16 weeks of gestation, hospitalized due to an anterior and lateral ST Elevation Myocardial Infarction (STEMI), complicated by SCA due to the mechanism of ventricular fibrillation. The patient was qualified for invasive reperfusion treatment which included left anterior descending (LAD) coronary artery surgery with drug eluting stent (DES) implantation and ballooning of the diagonal first coronary artery. Echocardiography done after treatment revealed apical hypokinesia and left ventricular ejection fraction of 70%. Subsequently the patient was kept under obstetrical and cardiological care. At 37 weeks of gestation, the pregnancy was finished by a successful caesarean section.       Pregnancy is a state of hypercoagulability and decreased activity of the fibrinolytic system.The clinical management in this case does not differ from the clinical procedure adopted for non-pregnant women. It is important to make a diagnosis quickly and implement a life-saving procedure as soon as possible.